Geotechnical Properties Of Raw And Processed Bauxite From Bukit Goh, Kuantan, Pahang; In Accordance With IMSBC Code - Muzamir, Hasan; Ahmad Amirul, Faez; M. Azizul, Moqsud; Tam, Weng Long; Phang, Biao Yu (GEOMATE International Society, 2018)
This research focuses on the differences of geotechnical properties between raw and processed Bukit Goh bauxite. As bauxite material has high clay content which mostly composed of silicate minerals, it has high risk to cause cargo liquefaction which in turn causes catastrophic incident. This paper includes the analysis of raw and processed bauxite where its fine particle contents has been minimized using beneficiation method to reduce the risk of liquefaction by referring to the International Maritime Solid Bulk Cargoes Code (IMSBC Code) standard. To analyse these characteristics of the bauxite, five samples were selected at Bukit Goh, Kuantan; three of the samples from the Bukit Goh mine and two samples from stock pile were tested to identify the bauxite geotechnical properties by referring to GEOSPEC 3: Model Specification for Soil Testing; particle size distribution, moisture content, specific gravity, morphological properties as well as its elemental and oxide properties. Laboratory tests involved including Small Pycnometer test, Dry Sieve test, X-ray fluorescence test (XRF) and Field emission scanning electron microscopy test (FESEM). The results show that average moisture content of raw bauxite is 24.81% which exceeded the recommended value of maximum 10% while the average moisture content of processed bauxite is only 6.69%. The average fine material for raw bauxite is 38.40% which should not be greater than 30% per IMSBC standard while for processed bauxite is 21.40%. In conclusion, the quality and safety of processed bauxite is better than raw bauxite.